Medical Records and Other Stories: a Narratological Framework - Kay, S.; Purves, I. N. (Methods of Information in Medicine, 1996)
A new model of the medical record is introduced which can incorporate context, structure, process and use of the medical record within a single narratological framework. It is claimed that the analysis of narrative and, in particular, the study of the story metaphor can provide a theoretical model which provides coherence within the broad discipline of Medical Informatics. It is argued that this framework maintains different levels of abstraction, is useful for teaching and clinical practice, and that its concepts can be readily understood by those in both lay and technical healthcare professions.
Keywords: Medical Record; Narrative; Medical Informatics; Theoretical Models